Clinical pharmacokinetic drug interaction studies of gabapentin enacarbil, a novel transported prodrug of gabapentin, with naproxen and cimetidine - Lal, Ritu (Blackwell Science Inc, 2010)
AIM: Gabapentin enacarbil, a transported prodrug of gabapentin, provides sustained, dose-proportional exposure to gabapentin. Unlike gabapentin, the prodrug is absorbed throughout the intestinal tract by high-capacity nutrient transporters, including mono-carboxylate transporter-1 (MCT-1). Once absorbed, gabapentin enacarbil is rapidly hydrolyzed to gabapentin, which is subsequently excreted by renal elimination via organic cation transporters (OCT2). To examine the potential for drug–drug interactions at these two transporters, the pharmacokinetics of gabapentin enacarbil were evaluated in healthy adults after administration alone or in combination with either naproxen (an MCT-1 substrate) or cimetidine (an OCT2 substrate). METHODS: Subjects (n= 12 in each study) received doses of study drug until steady state was achieved; 1200 mg gabapentin enacarbil each day, followed by either naproxen (500 mg twice daily) or cimetidine (400 mg four times daily) followed by the combination. RESULTS: When gabapentin enacarbil was co-administered with naproxen, gabapentin C(ss,max) increased by, on average, 8% and AUC by, on average, 13%. When gabapentin enacarbil was co-administered with cimetidine, gabapentin AUC(ss) increased by 24% and renal clearance of gabapentin decreased. Co-administration with gabapentin enacarbil did not affect naproxen or cimetidine exposure. Gabapentin enacarbil was generally well tolerated. CONCLUSIONS: No gabapentin enacarbil dose adjustment is needed with co-administration of naproxen or cimetidine.